JIKA SENGAJA BERBUAT DOSA MAKA TIDAK ADA KORBAN UNTUK MENGHAPUS DOSA ITU “IBRANI 10 : 26”: (Sebab jika kita sengaja berbuat dosa sesudah memperoleh pengetahuan tentang kebenaran, maka tidak ada lagi korban untuk menghapus dosa itu) - Tuti Christin; Decky Kansil (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The purpose of this study is to conduct a review of biblical theology about If we intentionally sin, after having received knowledge of the truth, then there is no more sacrifice to take away the sins Hebrews 10:26. In today's era, sin and evil have increasingly blinded the conscience of humans, both in all circles, there are small children who already know that lying is a sin but still do it without feeling guilty and it is not only done by small children, even adults who are diligent in worship also do so is a common thing and considered normal, sin and evil that are increasingly viewed lightly by all levels of humanity make the verses of God's Word must be increasingly proclaimed and reminded to all levels of humanity, a concrete example in responding to sin is a group of LGBT who consider that they have human rights and fight for their rights as LGBT must be recognized and protected by law, this does not only happen in foreign countries but in Indonesia it is also growing and spreading. In the view of certain people that Sin is killing, stealing, corruption, lying and committing immoral acts while LGBT is an act based on mutual consent and willingness then this is considered not a violation and not something that harms the opponent so it is not a sin because if the partner willingly wants to do the same thought it means no one is harmed so it is not a sin but a human right that must be defended and protected by law. This is very interesting and needs to be explained whether the act of viewing sin with this wrong view will result in a sin that will not be forgiven again if we refer to the book of Hebrews 10:26 "For if we sin willfully after having received the knowledge of the truth, there no longer remains a sacrifice for sins".